The Influence Of Work Discipline And Communication On Employee Performance Ahass Subur Jaya Marta Tasikmalaya City - Mala Amalia; Arga Sutrisna; Dudu Risana (Journal of Indonesian Management, 2023)
This study aims to determine the effect of work discipline and communication simultaneously on employee performance at Ahass Subur Jaya Marta Tasikmalaya City. Partial influence of work discipline and communication on employee performance at Ahass Subur Jaya Marta Tasikmalaya City. The method used in this research is quantitative with a descriptive and survey approach. With a research sample of 40 people as respondents to Ahass Subur Jaya Marta Tasikmalaya City based on 40 known population data. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS support application version 25. Simultaneously work discipline and communication have a significant effect on employee performance. Partially, the work discipline variable haspositive but not significant effect on employee performance. Communication variable, which partially has a significant effect on employee performance.